Protective Effect of Dimethyl Sulfoxide on Stricture Formation in Corrosive Esophageal Burns in Rats - Kilincaslan, Huseyin; Karatepe, Hande Ozgun; Sarac, Fatma; Olgac, Vakur; Kemik, Ahu Sarbay; Gedik, Ahmet Hakan; Uysal, Omer (European Journal of Pediatric Surgery, 2014)
Introduction The aim of this study was to investigate the effects of dimethyl sulfoxide (DMSO) on stricture formation in corrosive esophageal burns.Materials and Methods A total of 21 male rats were divided equally into three groups. In Group 1 (burn) and Group 2 (burn + DMSO) burns were induced in the distal esophagi with a 30% NaOH solution. In Group 3 (control), a saline solution was applied to the esophageal lumen. In Group 2, DMSO was administered intraperitoneally (3 mg/kg) 15 minutes after the burn was induced and then every 24 hours for 7 days. All rats were humanely killed at the end of Day 22. Distal esophagi were harvested for analysis. The stenosis index (SI) and histopathologic damage score were evaluated in addition to malondialdehyde (MDA), myeloperoxidase (MPO), nitric oxide (NO), tumor necrosis factor alpha (TNF-α), and interleukin-6 (IL-6) levels.Results DMSO significantly decreased the levels of MDA, NO, TNF-α, and IL-6 in the rats with burned esophagi. Furthermore, the SI and histopathologic scores decreased significantly in the burn + DMSO group relative to the burn group (p < 0.05).Conclusions Our results suggest that DMSO can decrease the occurrence of stricture formation and could represent a beneficial alternative therapy for the treatment of corrosive esophagitis.
Keywords: corrosive esophageal burn; dimethyl sulfoxide; esophageal stricture; oxidative stress